¿Cómo proteger jurídicamente al ser humano si se ignora su estructura existencial? - Fernández Sessarego, Carlos (2015)
The author makes a critical analysis of how over time it has tried to find the subject of study of Law and how it is distinguished from other beings that make up the universe. t hus the rational dimension of man has passed his ontological analysis as being in itself which makes it unique and spirit as the arrangement will be co-existential seeking protection for the same freedom he has. Finally, the author focuses on the own “freedom” of man and of which the other rights it has.